Optimal duration of therapy in the recovery period of vestibular diseases - M. V. Zamergrad; V. A. Parfenov; N. N. Yakhno (Неврология, нейропсихиатрия, психосоматика)
Dizziness is a common symptom in neurological and general medical practice. In most cases it is caused by diseases of the central or peripheral vestibular system. The most common vestibular system diseases include benign paroxysmal postural vertigo, dizziness, Meniere's disease, vestibular neuronitis, and cerebrovascular diseases. One of the main treatments for the diseases accompanied by dizziness is vestibular rehabilitation that is a complex of exercises, the goal of which is to stimulate vestibular compensation. Adequate vestibular compensation allows a patient to get rid of dizziness and unsteadiness even though vestibular system injury is irreversible. Some medications are able to enhance the efficiency of vestibular rehabilitation. At the same time, the optimal duration of treatment for the most common vestibular disorders has not beenadequately explored. The paper gives the results of an observational program, whose purpose was to determine the optimal duration of vestibular rehabilitation in combination with the use of tanakan in patients with non-progressive unilateral peripheral vestibular disorder.Patients and methods. Data on 46 patients aged 19 to 70 years who underwent vestibular rehabilitation and took tanakan for vertigo caused by vestibular neuronitis (n = 44), labyrinthitis (n =1), or Ramsay Hunt syndrome (n = 1) were analyzed. All the patients were examined four times. The symptoms were recorded and the histories of disease were considered. The degree of vestibular disorders, including vertigo, was assessed when collecting complaints. The symptoms of vertigo were objectivized using its vertigo rating scale and five-point subjective rating scale for vertigo. All the patients underwent standard somatic and neurological examinations and videonystagmography. During the first visit after diagnosis, vestibular exercises were chosen for the patients and tanakan was used in a dose of 40 mg thrice daily to accelerate vestibularcompensation. During visits 2, 3, and 4, the symptoms of the disease were recorded in the patients and the time course of treatment-induced changes in their status was estimated.Results. The optimal duration of treatment was established to be at least 2 months. Vestibular exercises in combination with the intake of tanakan resulted in a reduction in the symptoms of vestibular dysfunction and in emotional improvement in the patients.